Effects of topical hyaluronic acid on nasal mucosa wound healing - Sabig, Lidya; Dewi, Anna Mailasari Kusuma; Hariyati, Riece; Karlowee, Vega; Septarina, Faiza Rizky Aryani (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Chronic rhinosinusitis (CRS) is a chronic inflammatory disease of the nasal and paranasal sinuses mucosa that takes place for more than 3 months. The treatment paradigm nowadays depends on Functional Endoscopic Sinus Surgery (FESS) in the hope to repair the damaged mucosa, restoring it to its physiological condition. Hyaluronic Acid (HA) could restore the natural barrier of the mucosa and stop the inflammatory cascade. Purpose: To understand the difference in the number of inflammatory cells in the post-FESS nasal mucosa in CRS patients that had been treated with HA. Method: This was pre and post-test, double-blinded, randomized control group study design of 22 CRS patients (range 18 to 55 years) in Dr. Kariadi General Hospital, Semarang from May to August 2019. All subjects had undergone biopsies of the inferior turbinate at the time of surgery and 4 weeks after surgery. The number of pre and post-test neutrophil, eosinophil and lymphocyte counts were compared between control and treatment groups. The neutrophil-to-lymphocyte ratio (NLR) and eosinophil-to- lymphocyte ratio (ELR) levels were also compared between the two groups. Data analysis was done using the Wilcoxon test. Result: When the pre and post-test treatment group and the control group were compared, no statistically significant difference was found between two groups except for ELR in the treatment group (p=0.028). Conclusion: ELR was decreased significantly in the treatment group. NLR level was also decreased but not significant. This study had shown that topical HA could positively modulate the inflammatory response. Keywords: chronic rhinosinusitis, FESS, histopathology, neutrophil, eosinophil, lymphocyte ABSTRAK Latar belakang: Rinosinusitis kronis (RSK) merupakan penyakit inflamasi kronik pada mukosa hidung dan sinus paranasal yang berlangsung lebih dari 12 minggu. Bedah Sinus Endoskopi Fungsional (BSEF) pada RSK bertujuan untuk memperbaiki mukosa yang rusak dan mengembalikannya ke kondisi fisiologis. Asam hyaluronat (AH) dapat mengembalikan penghalang alami mukosa dan menghentikan proses inflamasi. Tujuan: Untuk mengetahui perbedaan jumlah sel inflamasi pada mukosa hidung pasca BSEF pada pasien RSK yang diberikan terapi tambahan AH. Metode: Penelitian ini merupakan penelitian pre dan post-test, tersamar ganda, desain penelitian kelompok kontrol acak terhadap 22 pasien RSK (berusia 18 hingga 55 tahun) di RS Dr. Kariadi, Semarang dari bulan Mei hingga Agustus 2019. Semua subjek dilakukan biopsi konka inferior pada saat operasi dan 4 minggu setelah operasi. Jumlah neutrofil, eosinofil, dan limfosit sebelum dan sesudah terapi dibandingkan antara kelompok kontrol dan kelompok perlakuan. Rasio neutrofil terhadap limfosit (NLR) dan rasio eosinofil terhadap limfosit (ELR) juga dibandingkan antara kedua kelompok. Analisis data dilakukan dengan menggunakan uji Wilcoxon. Hasil: Hasil perbandingan kelompok perlakuan dan kelompok kontrol sebelum dan sesudah terapi, menunjukkan tidak ada perbedaan yang signifikan secara statistik antara kedua kelompok kecuali ELR pada kelompok perlakuan (p=0,028). Kesimpulan: ELR menurun secara signifikan pada kelompok perlakuan. Tingkat NLR juga menurun tetapi tidak signifikan. Penelitian ini menunjukkan bahwa AH topikal dapat secara positif memodulasi respon inflamasi. Kata kunci: rinosinusitis kronis, BSEF, histopatologi, neutrofil, eosinofil, limfosit